Ageing, organisations and management : constructive discourses and critical perspectives - Aaltio-Marjosola, Iiris; Mills, Albert J., 1945-; Mills, Jean Helms, 1954- (Palgrave Macmillan, 2017)
"This book explores critical perspectives on ageing in organisations and offers both managerial and workplace practices for dealing with this prominent issue. The collection provides cross-disciplinary research on the discursive and mythological aspects of ageing at work as well as recent studies of the relationship between age and innovation, talent, careers, and workplace transitions. The book brings together authors from Europe, North America and Australia. By addressing current societal challenges and offering insights on ageing at work, this book will be of interest to those involved in human resource management, workplace organisation and the sociology of work."-- Provided by publisher.
8: Age in the City: Embodied Ageing in Financial Services.
Keywords: Older people -- Employment.; Age and employment.; elektronické knihy; electronic books